Rancang Bangun Fault Tolerance pada Sistem Database untuk Aplikasi Point Of Sale - Standy Oei; Ahmad Ashari (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2011)
Abstract— A fault tolerant system is a system that has the ability to be able to continue its jobs properly although there is a fault in hardware or software of the system. A system that has a fault tolerant capability is usually critical or important system. For example is at Point Of Sale application. Point Of Sale Application has evolved from offline-based toward online-based. With an online-based, the existence of a central database server must be guaranteed free from failure.To get a central database server that is free from failure is impossible. Something that can be cultivated is to create a system that can tolerate a failure in the central database server. This is done with the help of a second central database server (slave), which is useful as a replication of the central database server (master). To ensure data from these two central database servers are the same, then used the concept of reading and writing "read one/write all". And to manage all the processes needed in implementing a fault tolerant application, we need the help from a coordinator.The result obtained in this research is a design of fault tolerant architecture that can be applied to various types of information system applications include Point Of Sale application. By using this fault tolerant architecture that has been built, Point Of Sale application can still run the transaction process even if there is a failure in accessing data in one central database server (master/slave). Keywords— fault tolerance, database system, point of sale application